Environmental impacts of tilapia fish cage aquaculture on water physico-chemical parameters of Lake Kivu, Democratic Republic of the Congo - Lubembe, Sharon Indasi; Walumona, Jacques R.; Hyangya, Béni Lwikitcha; Kondowe, Benjamin N.; Kulimushi, Jean-Diste M.; Shamamba, Giséle A.; Kulimushi, Alain M.; Hounsounou, Belinda H. R.; Mbalassa, Mulongaibalu; Masese, Frank O.; Masilya, Mulungula Pascal (Frontiers in Water, 2024)
In Africa, cage aquaculture has been growing due to its potential to address food insecurity concerns, provide livelihoods, and contribute to local economies. However, there is a need for continued research on the sustainability and potential ecological effects of cage aquaculture in African lakes and reservoirs.Even with an adequate amount of water, lakes and reservoirs cannot provide ecosystem services if the water quality is not properly managed. The current study on Lake Kivu, DRC focuses on understanding the effects of tilapia cage aquaculture on selected water quality physico-chemical parameters of water in the Bukavu sub-basin, DRC. The research was conducted in both caged and uncaged sampling stations, on the spatial and temporal scale from April to September 2023 at three bays serving as sampling stations: two caged (Ndendere, Honga) and one non-caged (Nyofu). Some physico-chemical parameters were measured in situ, whereas chlorophyll a and nutrients analysis were performed at the Institut Supérieur Pédagogique (I.S.P) laboratory in Bukavu. The parameters were used to calculate water quality indices: the water quality index (WQI) to classify the water quality at the stations, the organic pollution index (OPI) to determine the level of organic pollution, the Carlson's Trophic Status Index (CTSI) to classify the trophic state of the stations. Chlorophyll a concentration was a measure of algal biomass. All physicochemical parameters apart from DO, ammonium and temperature showed no significant differences among stations and depths. Interaction between stations and between seasons was only observed on turbidity. The WQI for all the sampling stations ranged from medium to good quality (51-90). The OPI for all stations showed minimal level of pollution (4.6-5.0) hence lake's water still organically unpolluted.CTSI results indicated the sampling stations are in a eutrophic state 50 to 70) . Fish cage aquaculture does not yet pose harm to the water quality of the two Lake Kivu stations under consideration, according to the study's findings. However with the anticipated growth of cage fish farming activities to meet the rising fish demand, continuous monitoring of water quality in the Lake should be done to inform management decisions and for sustainable aquaculture..